THE INFLUENCE OF STUDENT MANAGEMENT ON PSYCHOLOGICAL WELL BEING - Masruroh, Durrotul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
One of the problems in education that has a considerable influence is depression in students. Whether it is due to personal problems in the family or unpleasant school experiences, it can also be a source of stress and reduce students' quality of life at school and in their home environment. This study examines the